Scientific representation : paradoxes of perspective - Van Fraassen, Bas C. (Oxford University Press, 2010)
Bas C. van Fraassen presents an original exploration of how we represent the world. Science represents natural phenomena by means of theories, as well as in many concrete ways by such means as pictures, graphs, table-top models, and computer simulations. Scientific Representation begins with an inquiry into the nature of representation in general, drawing on such diverse sources as Plato's dialogues, the development of perspectival drawing in the Renaissance, and the geometric styles of modelling in modern physics. Starting with Mach's and Poincare's analyses of measurement and the 'problem of coordination', van Fraassen then presents a view of measurement outcomes as representations. With respect to the theories of contemporary science he defends an empiricist structuralist version of the 'picture theory' of science, through an inquiry into the paradoxes that came to light in twentieth-century philosophies of science. Van Fraassen concludes with an analysis of the complex relationship between appearance and reality in the scientific world-picture.